Detection and antifungal susceptibility of Cryptococcus spp. in some public centers in the Federal District (REMUNOM, 2025)
Cryptococcosis is a fungal disease caused by the species Cryptococcus neoformans, which can affect various organs, especially the lungs and central nervous system. Transmission occurs through the inhalation of dehydrated yeasts dispersed in the form of aerosols and the largest reservoir of this fungus is birds, such as pigeons, making the disease cosmopolitan. The growing number of cancer patients and the increase in AIDS cases in Brazil make this infection dangerous, due to the difficulty in diagnosing it early and/or the rapid worsening of the infection due to immunosuppression. In view of the above, this study sought to detect Cryptococcus spp. in public places with a large flow of people and birds, as well as carrying out antifungal sensitivity tests. Fifty samples were collected from hospitals, bus stations and tourist attractions. The results of the microbiological analysis were: 8 samples (16%) positive for the microorganism. After statistical analysis (Fischer), the evidence found suggests that the presence of the fungus is not uniform among the sites collected, some are more associated with the presence of the microorganism than others, demonstrating a variation in the distribution of Cryptococcus spp in the environment, requiring further investigation into factors that influence its presence or absence in different environments. The fungal sensitivity tests showed a high resistance profile to azole antifungals, such as Fluconazole (25mcg) and Itraconazole (10mcg), for Nystatin (100 I.U.) and Miconazole (50mcg) the strains tested showed a sensitive and intermediate profile after 24 hours of incubation, demonstrating the versatility that the microorganism has, especially in environmental sources.